2018
DOI: 10.1097/iop.0000000000001039
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Early Postoperative Eyelid Position on Late Postoperative Result in Mueller’s Muscle Conjunctival Resection and External Levator Advancement Surgery

Abstract: Both external levator resection and MMCR can effectively elevate the eyelid in cases of primary involutional ptosis, and have similar late postoperative results. The authors found that MMCR cases undergo greater change between the early and late postoperative period, suggesting the process of eyelid elevation after MMCR may be dynamic, involving postoperative physiologic modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Some patients only had a single set of post-operative eyelid measurements documented around post-operative day 7. However, the majority of patients in our study underwent levator advancement ptosis repair, and Danesh et al 35 found that the MRD1 did not change between the post-operative week 1 and month 3 visits after levator advancement. We did not use a standardized tool to assess subjective improvement, and had to depend on documentation of patient comments in the post-operative notes.…”
Section: Discussionmentioning
confidence: 55%
“…Some patients only had a single set of post-operative eyelid measurements documented around post-operative day 7. However, the majority of patients in our study underwent levator advancement ptosis repair, and Danesh et al 35 found that the MRD1 did not change between the post-operative week 1 and month 3 visits after levator advancement. We did not use a standardized tool to assess subjective improvement, and had to depend on documentation of patient comments in the post-operative notes.…”
Section: Discussionmentioning
confidence: 55%
“…Studies have defined MMCR success using subjective terminology 2,4 or arbitrary cosmetic scales. 13 In addition, when MRD1 is documented, the outcome most often reported is the change in MRD1 from baseline [3][4][5]7,10,[13][14][15][16][17][18][19] -a measure that does not adequately reflect the likelihood of obtaining a clinically acceptable result. Although racial variations exist for upper eyelid height, 2 standard deviations below the mean normal MRD1 is thought to lie between 2.0 and 2.5 mm, 20,23 and lay observers typically recognize upper eyelid asymmetry when the difference in MRD1 exceeds 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…3–5,7,10,13–19 These studies document that, on average, MMCR surgery increases baseline MRD1 by 1.5–2 mm. 3–5,7,10,13–19 Although the purpose of blepharoptosis surgery is to increase MRD1, the mean change in MRD1 is not a telling indicator of operative success. Mean change in MRD1 neither describes how likely a patient is to achieve an acceptable final eyelid height nor does it convey information about symmetry.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Danesh et al compared early and late lid height in patients undergoing MMCR or external levator resection and made the interesting observation that whilst one third of patients undergoing MMCR had less than 0.5 mm elevation at 1 week, approximately one quarter of patients having undergone MMCR procedures, had increasing lid height by 1 mm or more between the 1 week and 3‐month follow‐up. The group concluded that the lid height at 1 week does not necessarily reflect the final outcome after MMCR and patients should be counselled accordingly.…”
Section: The Aponeurosis Vs Müller's Muscle In Ptosis Correctionmentioning
confidence: 99%